Skeletal muscle satellite cells: Mediators of muscle growth during development and implications for developmental disorders. Issue 5 (November 2014) - Dayanidhi, Sudarshan; Lieber, Richard L.
ABSTRACT Satellite cells (SCs) are the muscle stem cells responsible for longitudinal and cross‐sectional postnatal growth and repair after injury and which provide new myonuclei when needed. We review their morphology and contribution to development and their role in sarcomere and myonuclear addition. SCs, similar to other tissue stem cells, cycle through different states, such as quiescence, activation, and self‐renewal, and thus we consider the signaling mechanisms involved in maintenance of these states. The role of the SC niche and their interactions with other cells, such as fibroblasts and the extracellular matrix, are all emerging as major factors that affect aging and disease. Interestingly, children with cerebral palsy appear to have a reduced SC number, which could play a role in their reduced muscular development and even in muscular contracture formation. Finally, we review the current information on SC dysfunction in children with muscular dystrophy and emerging therapies that target promotion of myogenesis and reduction of fibrosis. Muscle Nerve50: 723–732, 2014